Nymphal development of Podisus connexivus Bergroth fed on the cotton leafworm - dos Santos, Terezinha M.; Silva, Evandro do N.; Ramalho, Francisco de Sousa (Pesquisa Agropecuaria Brasileira, 1995)
Nymphal development of Podisus connexivus was studied on second, third, fourth and fifth instar larvae of cotton leafworm Alabama argillacea. The duration of the nymphal phase was inversely proportional to the age of the prey. The number of the preyed larvae by P. connexivus decreased in proportion to the prey age increased. High rates of survival of the predator in each instar was verified as feeding on each one of the different diets. The cotton leafworm is an adequate prey for the nymphal development of P. connexivus. The prey size is an important component in the predation process for all instars of the P. connexivus.